Heterologous Expression of Aldehyde Dehydrogenase from Saccharomyces cerevisiae in Klebsiella pneumoniae for 3-Hydroxypropionic Acid Production from Glycerol - Wang, Kang (Springer-Verlag, 2012)
3-Hydroxypropionic acid (3-HP) is a commercially valuable platform compound. Klebsiella pneumoniae has been concerned as an appropriate host for 3-HP production because of its robust capacity to metabolize glycerol. Glycerol conversion to 3-HP in K. pneumoniae comprises two successive reactions: glycerol dehydratase catalyzes glycerol to 3-hydroxypropionaldehyde (3-HPA); aldehyde dehydrogenase catalyzes 3-HPA to 3-HP. Previous studies focusing on inducible expression of aldehyde dehydrogenase have shown defects of high cost of inducer and low catalytic activity due to inclusion body. Here we show a different strategy that a native promoter in the host K. pneumoniae was used to drive the heterologous expression of aldehyde dehydrogenase gene ald4 from Saccharomyces cerevisiae. The 3-HP yield of the recombinant reached a peak of 4.23 g/L at log phase, but it decreased during later period of fermentation. Except the validation of high activity of ald4, particularly, the 3-HP formation was uncovered to be closely coupled with cell division, and the lacking of NAD and ATP at latter fermentation phase became the bottleneck for cell growth and 3-HP accumulation. Furthermore, 3-HP is postulated to be converted to 3-HPA via feedback inhibition or other metabolite via unknown mechanism. Since glycerol dissimilation is a common mechanism in a variety of bacteria, the expression strategy using native promoter and implications may provide significant insight into the metabolic engineering for 3-HP production. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12088-012-0280-0) contains supplementary material, which is available to authorized users.